Non-Performing Financing Syariah: A Paradigm Analysis of Capital Adequacy Ratio and Finance to Deposit Ratio - Lifinda Ayuning Putri , Intan; Jazuli , A Muhamad; Aji , Suseno (Research Horizon, 2025)
This study aims to examine the effect of Capital Adequacy Ratio (CAR) and Finance to Deposit Ratio (FDR) on Non-Performing Financing (NPF) moderated by return on assets (ROA). The sample of this research is Islamic banking registered with the Financial Services Authority in 2019-2023. This study uses multiple linear regression data analysis techniques with SPSS. The results showed that CAR has a positive effect on NPF while FDR has no effect on NPF. ROA only moderates the relationship between CAR and NPF. The results of this research can be a means of highlighting the effectiveness of NPF which can be improved through CAR and strengthened with ROA so that it can contribute to corporate banking as a whole.